Radiation of Ultra-Wideband (UWB) Signals - Immoreev, I.J.; Sinyavin, A.N. (Радиофизика и радиоастрономия, 2002)
The radiation of short duration signals (or ultra-wideband – UWB signals) is significantly different from the long duration narrowband signals (see Table 1 below). Paper analyzed the processes in linear antennas and gives a physical interpretation these differences.